DOMINASI WACANA ANTI-POLITIK BARAT PADA MEDIA-MUSLIM REVIVALIS (Analisis Wacana Model Teun Van Dijk Tabloid Media Umat Edisi Pemilu 2014) - Karman Karman (BPSDMP Kominfo Jakarta, 2014)
Indonesia as a democratic country has conducted general elections since 1955. Democracy originating from Greece has globalized. In other word, it becomes grand narratives. In Indonesia, muslim media responds democracy differently. Some media denies it because of spirit to implement islam totally (revivalism). Media Umat tabloid is a media which voice discourse of ant-western politic (anti-democracy). This article dealts with how media delegitimize democracy as product of the West, and what the reasons media delegitimize it. This discourse analysis harnesses analysis model introduced by Teun Van Dijk. This one focuses on textual structure. This research shows that Media Umat Tabloid focuses to delegitimize political parties because of their inability to make an improvement for Indonesia. According to Media Umat, The root cause is secularism & capitalism. The argumentation to delegitimize based on two different contexs. First, performance of political and legal institutions do not make an improvement and welfare. Oppositely, they do corruptive actions. Democracy tends to be on the side of capitalist and only and brings about demagogue. Second, delegitimzation on the basis of theological argument that democracy is incompatible with Islamic canon (syari’ah). Indonesia sebagai negara demokratis sudah menyelenggarakan proses pemilihan umum. Demokrasi yang berasal dari bangsa Yunani kini menjadi sistem yang mendunia, grand narratives. Di Indonesia, konsep ini mendapat penolakan dari umat islam. Penolakan ini dikaitkan dengan semangat untuk kembali ke sistem Islam secara total (revivalisme). Tabloid Media Umat adalah media yang menyuarakan wacana anti-demokrasi. Tulisan ini akan membahas bagaimana wacana delegitimasi sistem demokrasi sebagai produk Barat dilakukan oleh media tersebut, dan bagaiama media ini melakukan delegitimasi demokrasi. Penelitian menggunakan analisis wacana model Van Dijk yang fokus pada analisis struktur teks. Kesimpulan penelitian ini menunjukkan bahwa Tabloid MU mendelegitimasi Partai politik yang dinilai tidak akan menciptakan kemajuan dan menyelesaikan persoalan bangsa. Sebab, akarnya terletak pada sistem yang sekuler dan kapitalistik. Delegitimasi demokrasi didasarkan pada dua konteks yang berbeda. Pertama, kinerja lembaga politik dan hukum tidak mampu memberikan kemajuan dan kesejahteraan tapi malah berbuat korup. Demokrasi selalu berpihak kepada pemilik modal, dan melahirkan para demagogue. Kedua, delegitimasi atas dasar teologis. Demokrasi tidak sesuai dengan hukum Islam.